Usia Perjanjian Lama - Nepho Gerson Laoly (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2019)
Why was the Old Testament established in the 1st century AD, long after its use for the Israelites. Then, if there are determined to be part of the Old Testament, then at least there are writings that do not meet the conditions. The existence of rejected writings is increasingly confirmed by the existence of the Song of Songs and the Ecclesiastes who at the last moment were "accepted" as part of the Old Testament. Why the books that have been rejected at Jamnia do not return to use or if possible then re-consider them in the Old Testament canon. Because of course the development of knowledge that is more "sophisticated" than the 1st century AD, will be able to reveal the "truth" so that the addition of new books is possible. Isn't this all just talking about setting standards that can be changed in accordance with a mutual agreement. We must see evidence from the writings of Josephus namely Apionem, Edras, Daniel, Sirach, Jamnia, and the Samaritan Pentateuch. With this work, may the Old Testament is increasingly confirmed as a valid collection.